Effectiveness of Government Supervision and Guidance for Mass Organizations: Case Study in West Java - Septi Wulandari; Nandang Alamsah Deliarnoor; Neneng Yani Yuningsih (Dinasti Publisher, 2025)
Mass organizations are organizations that are established and formed by the community voluntarily and function as a forum for community aspirations for social, educational, religious, or cultural activities. There are 116,647 mass organizations in West Java out of 554,692 registered mass organizations spread across Indonesia. The purpose of this study is to see how and to what extent the effectiveness of the supervision and guidance carried out by the West Java government is running towards mass organizations. This study uses a descriptive qualitative approach with a literature study method, the aim is to understand in depth a social phenomenon reported in online media, and to strengthen the analysis with theories and findings from scientific sources. The results of the study indicate that the effectiveness of the supervision and guidance functions carried out by the local government towards mass organizations is still low. Therefore, a policy reorientation is needed through a risk-based supervision model, integration of an integrated database system between agencies for real-time monitoring of mass organization activities, initiation of a tripartite collaborative forum (government-mass organizations-academics) as a space for constructive dialogue and early conflict resolution, and increasing the capacity development of officers through specific training for contemporary-based coaching officers.